CORRELATION BETWEEN OHS KNOWLEDGE, MOTIVATION, WORK STRESS, AND UNSAFE ACTION (STUDY ON PRODUCTION SECTION WORKERS AT PT MANDIRI JAVA FOOD SEMARANG, INDONESIA): A CROSS-SECTIONAL STUDY - Pawening, Ayu Sekar; Martiana, Tri (Journal of Public Health Research and Community Health Development, 2023)
ABSTRACT Background: As the industrial revolution 4.0 began, technology began to grow, and company owners began to develop their use of technology and human resources. According to the 8th Sustainable Development Goal's targets concerning decent work and economic growth, it is necessary to achieve targets related to protecting workers' rights and supporting a safe working environment for all workers, including prevention of work accidents. One of the causes of work accidents is unsafe action in the food industry as PT Mandiri Java Food Semarang that can be caused by personal factors, including knowledge of occupational health and safety (OHS), motivation, and work stress. Purpose: This study analyzes the correlation between OHS knowledge, motivation, and work stress with unsafe actions experienced by production workers at PT Mandiri Java Food Semarang. Method: This type of research was descriptive observational research with a cross-sectional design using spearman correlation test. The sample of the study was all the total population of the production workers (37 people). Results: The results showed a weak correlation between OHS knowledge and unsafe action (r = -0.351). Moderate category correlation between motivation (r = -0.491) and work stress (r = 0.479) with unsafe action. Conclusion: This study concludes that OHS knowledge, motivation, and work stress are correlated factors and contribute to the occurrence of unsafe actions carried out by workers in the production sector of PT Mandiri Java Food Semarang.